Frontiers in occupational health and safety : introduction to occupational health hazards - Zahir, Farhana (Singapore : Bentham Books, 2019)
The definition of occupational health hazards is constantly changing over time as technology advances and as the awareness of work place safety issues continues to grow. Introduction to Occupational Health Hazards focuses on work-related hazards which have evolved with the advent of more recent professions. The book introduces readers to the basic concept of occupational hazards. From this starting point, readers are introduced to the types of medical disorders that can occur as a result of occupational hazards, such as cancer and neurological disorders.
Chapter 1. New Frontiers in Occupational Disease -- Chapter 2. Occupational Hazards as neurological disorders -- Chapter 3. Cancer as an Occupational Hazard -- Chapter 4. Occupational Health Hazards to medical and paramedical -- Chapter 5. Biosafety issues for scientists and laboratory workers -- Chapter 6. Stress and Compromised Mental Health as the New age Occupational Hazard.
Includes index.
Keywords: INDUSTRIAL HYGIENE